Oil-water flow regimes in 4-mm borosilicate glass and fluorinated ethylene propylene channels: Effects of wall wettability - Riley, G.A.; Bultongez, K.K.; Derby, Melanie M. (My University, 2019)
Formation water, found in oil deposits, is highly corrosive. By utilizing flow phenomena and surface tension forces in smaller channels (e.g., Eötvös number less than one), these fluids can be separated, thus altering corrosion and the pressure required for transport. This research investigates the effects of wall wettability on oil-water flow regimes and pressure drops. Oil-water flows were studied in 3.5-mm hydrophilic borosilicate glass and 4.0-mm hydrophobic fluorinated ethylene propylene (FEP) channels using Parol 100 mineral oil (i.e., density of 840 kg/m3 and viscosity of 0.0208 Pa s) and tap water (i.e., 997 kg/m3 and a viscosity of 0.001 Pa s). For these oil-water combinations, glass was water wetting (i.e., contact angle of 67° for a water droplet submerged in oil on glass) and FEP was water repelling (i.e., contact angle of 93° for a water droplet submerged in oil on FEP) under static conditions. Flow regimes and pressure drops were recorded for a range of oil superficial velocities [i.e., 0.31–3.7 m/s (glass) and 0.23–2.7 m/s (FEP)] and water superficial velocities [i.e., 0.080m/s–5.5 m/s (glass) and 0.060–5.5 m/s (FEP)]. Stratified, intermittent, annular, and dispersed flow regimes were observed in both tubes. Additional inverted and dual flow regimes were observed in the hydrophobic FEP; oil wetted the wall in inverted flows, and flow regimes occurred inside of another flow regime in dual flows (e.g., inverted-annular intermittent). The modified Weber number indicated whether the walls were wetted by oil, mixed oil and water, or water. Pressure drops were found to be correlated to the flow regime with increased pressure drops observed when oil fully or partially wetted the wall.
Citation: Oil-water flow regimes in 4-mm borosilicate glass and fluorinated ethylene propylene channels: Effects of wall wettability - ScienceDirect. (n.d.). Retrieved February 12, 2019, from https://www.sciencedirect.com/science/article/pii/S0920410518309070?via%3Dihub
Keywords: Multiphase Flow; Fluid Dynamics; Oil-Water interface; Capillarity